2013
DOI: 10.1371/journal.pone.0057931
|View full text |Cite
|
Sign up to set email alerts
|

Thermometry of Red Blood Cell Concentrate: Magnetic Resonance Decoding Warm Up Process

Abstract: PurposeTemperature is a key measure in human red blood cell concentrate (RBC) quality control. A precise description of transient temperature distributions in RBC units removed from steady storage exposed to ambient temperature is at present unknown. Magnetic resonance thermometry was employed to visualize and analyse RBC warm up processes, to describe time courses of RBC mean, surface and core temperatures by an analytical model, and to determine and investigate corresponding model parameters.MethodsWarm-up p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…4 However, the 30-minute rule as a time-based surrogate for temperature monitoring of RBC concentrates does not take into account a multitude of parameters besides time that influence individual RBC concentrate warming: volume and width of the RBC concentrate storage bag, thermal isolation (eg, air cushion envelopes), sample handling, and exact storage and ambient temperatures the RBC concentrates are exposed to, including variations in air conditioning and solar radiation. [5][6][7][8] In addition, the dynamics of RBC concentrate warming also depend on the number of units packed together. 9 Thus, time-based rules potentially contribute to unnecessary wastage, since RBC concentrates will be discarded even if core temperature is still within acceptable limits, and may be detrimental for patient safety, since RBC concentrates with elevated core temperatures may remain undetected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4 However, the 30-minute rule as a time-based surrogate for temperature monitoring of RBC concentrates does not take into account a multitude of parameters besides time that influence individual RBC concentrate warming: volume and width of the RBC concentrate storage bag, thermal isolation (eg, air cushion envelopes), sample handling, and exact storage and ambient temperatures the RBC concentrates are exposed to, including variations in air conditioning and solar radiation. [5][6][7][8] In addition, the dynamics of RBC concentrate warming also depend on the number of units packed together. 9 Thus, time-based rules potentially contribute to unnecessary wastage, since RBC concentrates will be discarded even if core temperature is still within acceptable limits, and may be detrimental for patient safety, since RBC concentrates with elevated core temperatures may remain undetected.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the 30-minute rule, core temperature of RBC concentrates removed from refrigerated storage at 6°C will remain below 10°C during a 30-minute exposure only if ambient temperature does not exceed 20°C. 8 Consequently, time-based rules can contribute to unnecessary wastage and are potentially detrimental to patient safety. TIs can address these issues since they monitor temperatures of individual RBC concentrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, it has also been suggested that time‐based rules can result in reissuing RBC units not maintained within the appropriate temperature range . In addition, time‐based rules do not take into account other parameters affecting RBC warming, including unit volume, bag width, unit handling, fluctuation in ambient temperature during transport, and number of units packed together during transport …”
mentioning
confidence: 99%